Central and Peripheral Routes to Advertising Effectiveness: The Moderating Role of Involvement - Petty, Richard E.; Cacioppo, John T.; Schumann, David (Journal of Consumer Research, 1983)
Undergraduates expressed their attitudes about a product after being exposed to a magazine ad under conditions of either high or low product involvement. The ad contained either strong or weak arguments for the product and featured either prominent sports celebrities or average citizens as endorsers. The manipulation of argument quality had a greater impact on attitudes under high than low involvement, but the manipulation of product endorser had a greater impact under low than high involvement. These results are consistent with the view that there are two relatively distinct routes to persuasion.